Penguatan Kelembagaan Badan Usaha Milik Nagari (BUM-Nag) Sebagai Upaya Peningkatan Ekonomi Nagari - Pratiwi Nurhabibi; Boni Saputra; Hidayatul fajri (Universitas Lancang Kuning, 2020)
Abstract Nagari-Owned Enterprises (BUM-Nag) or in most regions in other provinces known as Desa-Owned Enterprises (BUM-Des) is a manifestation of the mandate of Law Number 6 of 2014 concerning Villages, where the village government, in this case, Nagari is prosecuted accordingly Mandiri to be able to explore the wealth and potentials that exist in the Nagarinya area to be used as assets and sources of Nagari's financial income and is required to be able to carry out Nagari's financial management independently. BUM-Nag is an alternative business entity that needs to be developed to encourage the Nagari economy, with the hope of creating new economic resources for Nagari to utilize and to prosper the Nagari people's economy. This service activity aims to contribute thoughts and counseling about strengthening the BUM-Nag institution as a form of effort in improving the nagari economy. Service activities were carried out in Nagari Tabek Patah and Nagari Situmbuk, Salimpaung Subdistrict, Tanah Datar District. This activity uses the participatory rural appraisal (PRA) method, assistance, and counseling by looking at the potential possessed by Nagari as a creative business unit of the community and the potential that must be optimized. The result to be achieved from this empowerment activity is to increase the knowledge and capability or capacity of Nagari's apparatus on institutional strengthening and management of BUM-Nag as a form of effort in improving Nagari's economy